OP0124 RISK OF MALIGNANCIES ACROSS BIOLOGIC CLASSES IN RHEUMATOID ARTHRITIS: ANALYSIS OF A NATIONAL CLAIM DATABASE. (2nd June 2020) - Seror, R.; Fautrel, B.; Lafourcade, A.; De-Rycke, Y.; Mariette, X.; Tubach, F.
Abstract : Background: Objectives: To estimate the incidence rate of malignancies in biologic-treated RA patients, and to compared it to the general population and across different classes of biologics Methods: We conducted an historical cohort study within the French the national claim database, named SNDS. This database prospectively records individual health resource of 86% of the entire French population (65 million inhabitants) since 2007. RA adult patients were identified based on ICD-10 code (M05 or M06). Patients with cancer history were excluded. Treatment exposures focused on incident first use of biologics including all anti-TNF, rituximab, abatacept, tocilizumab, ustekinumab, anakinra. To identify incident treatment periods, only patients who did not receive any biologics in the 1-year period before the index date were selected. In the base case analysis, exposure was defined with a 90-day latency after treatment initiation and a 180-day carry-over period after drug discontinuation. To compare the risk of malignancies between biologic treated patients and general population, Standardized incidence ratio (SIR [95%CI]) were calculated using FRANCIM ("France Cancer Incidence et Mortalité") estimations as reference. To compare the risk of malignancies between biologics, a propensity score (including age, sex, year of first occurrence of RA code, date of treatment initiation, number of previous DMARDs, Charlson comorbidity index, diagnosis of tobacco and/or alcohol-associated disorders, number of hospitalizations for RA, cumulative corticosteroid dose) was calculated for each comparison. Hazard Ratios (HRs) for risk of cancer were estimated using Cox proportional hazard model using inverse probability of treatment weighting (IPTW) with propensity score. Exposure was considered as a time-dependent variable and propensity scores were estimated dynamically using pooled logistic regression reassessed for each new exposure. Results: Between 2007 and 2016, 31, 792 patients (112, 802 patient-years)- were exposed to biologics. The annual incidence rate of overall malignancies was 0.865 per 100 patients-years. Malignancies occurred in 730 patients exposed to anti-TNF, 235 patients exposed to another biologic and 11 exposed to both. As compared to the general population, biologic treated patients had an increased risk of lung cancer (SIR=1.35 [1.14;1.60]), a decreased risk of pancreatic cancer (SIR=0.52[0.31-0.85]) and no significant increased risk of invasive melanoma (SIR=1.15 [0.82;1.61]). Results were similar for anti-TNF-treated patients. Other biologics were not analyzed separately due to small sample sizes. The overall risk of malignancies and risk of lymphoma did not differ between anti-TNF and other biologics (analysed all together), or abatacept. Within the anti-TNF class, the overall risk of malignancies and risk of lymphoma did not differ between etanercept and monoclonal anti-TNF (table). Conclusion: Using a large nationwide healthcare database, representative of the French population, the overall risk of malignancies did not seem to differ across the different classes of biologic. Among anti-TNF, the risk of malignancies of lymphoma did not differ between etanercept and monoclonal antibodies. The risk of organ specific cancers, except lung cancer, did not differ from that of general population. Disclosure of Interests: Raphaèle Seror Consultant of: BMS, Medimmune, Novartis, Pfizer, GSK, Lilly, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB, Alexandre Lafourcade: None declared, yann de-rycke: None declared, Xavier Mariette Consultant of: BMS, Gilead, Medimmune, Novartis, Pfizer, Servier, UCB, Florence Tubach Grant/research support from: Florence TUBACH is head of the Centre de Pharmacoépidémiologie (Cephepi) of the Assistance Publique – Hôpitaux de Paris and of the Clinical Research Unit of Pitié-Salpêtrière hospital, both these structures have received research funding, grants and fees for consultant activities from a large number of pharmaceutical companies, that have contributed indiscriminately to the salaries of its employees. Florence Tubach didn't receive any personal remuneration from these companies.